2023
DOI: 10.3390/plants12122235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar Type, Concentration and Washing Conditions on the Germination Parameters of Three Model Crops

Abstract: Biochar has been recognized as a promising and efficient material for soil amendment. However, its effects on seed germination are variable due to its alkaline pH and/or the presence of phytotoxic substances. In this study, two types of biochar (B1 and B2) were mixed with soil at different concentrations (0%, 5%, 10%, 25%, 50% and 100%, w:w), and both the solid and liquid fractions of these mixtures were tested on the germination of basil, lettuce and tomato seeds. Furthermore, solid fractions subjected to a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Washing can be categorized into two types based on the type of washing agent used: water washing and chemical washing [129]. Water washing is the simplest and most common method.…”
Section: Removing Phytotoxicity By Washingmentioning
confidence: 99%
See 1 more Smart Citation
“…Washing can be categorized into two types based on the type of washing agent used: water washing and chemical washing [129]. Water washing is the simplest and most common method.…”
Section: Removing Phytotoxicity By Washingmentioning
confidence: 99%
“…Usually, the higher the concentration of the washing agent, the better the removal effect, but a too-high concentration of the washing agent may cause damage to the material. Therefore, it is necessary to choose a suitable washing agent and dosage based on the characteristics of pollutants and the tolerance of substrates or plants [129]. Moreover, the washing temperature and pH will affect the chemical reaction rate and equilibrium state between pollutants and washing agents [139].…”
Section: Soluble Organic Mattermentioning
confidence: 99%
“…Although its physicochemical properties depend on the raw material, preparation temperature, and preparation method [7,8], biochar generally has a porous structure, a high specific surface area (SSA), and rich surface functional groups. Studies have shown that biochar application can improve soil structure, water and nutrient retention, and fertility [9,10], mitigate abiotic and biotic stresses (e.g., salinity, pollution, and pathogens) in plants [11], and reduce chemical fertilizer application without causing yield loss [12][13][14][15][16][17][18][19]. Biochar generally has a high pH and thereby is alkaline in nature.…”
Section: Introductionmentioning
confidence: 99%